ANALISIS KINERJA KEUANGAN PADA BADAN KERJASAMA ANTAR DESA (BKAD) KECAMATAN BARENG KABUPATEN JOMBANG TAHUN 2018-2021 - Fitriah, Nurul (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose of this study is to analyze the financial performance of BKAD Bareng District, Jombang Regency in 2018-2021. The research approach used is quantitative by using a descriptive type of research. The subject of this study was BKAD, Bareng District, Jombang Regency. The object of this study is financial performance which includes liquidity ratio and activity ratio. Data collection uses documentation which is further analyzed using financial ratios. The results of this study revealed that the ratio of liquidity and activity ratio increased to financial performance. This research has a novelty, namely the addition of a variable previously studied by Endang Ambar Wati entitled "Financial Performance Analysis Using Liquidity Ratios in Bumdes Makmur Sejahtera Desa Kepenuhan Raya 2011-2015". The previous study only examined the liquidity ratio variables whereas, this study examined liquidity ratios and activity ratios. The results of this study are expected to be used as a reference to improve the financial performance of the Inter-Village Cooperation Agency (BKAD) of Bareng District, Jombang Regency.